Circular RNA cir-ITCH Is a Potential Therapeutic Target for the Treatment of Castration-Resistant Prostate Cancer. (21st August 2020) - Li, Shoubin; Yu, Chunhong; Zhang, Yunxia; Liu, Junjiang; Jia, Yi; Sun, Fuzhen; Zhang, Panying; Li, Jingpo; Guo, Liuxiong; Xiao, Helong; Gao, Fei; Deng, Xinna; et al.
Abstract : cir-ITCH, a well-known tumor-suppressive circular RNA, plays a critical role in different cancers. However, its expression and functional role in prostate cancer (PCa) are unclear. Herein, we explored the potential mechanism and tumor-inhibiting role of cir-ITCH in PCa. Using reverse transcriptase polymerase chain reaction assay, we analyzed the expression of cir-ITCH in PCa and paired adjacent nontumor tissue samples resected during surgical operation, as well as in two cell lines of human PCa (LNCaP and PC-3) and the immortalized normal prostate epithelial cell line (RWPE-1). Cell viability and migration of PCa cell lines were evaluated using CCK-8 and wound-healing assays. Expression of key proteins of the Wnt/ β -catenin and PI3K/AKT/mTOR pathways was detected using western blotting. We found that cir-ITCH expression was typically downregulated in the tissues and cell lines of PCa compared to that in the peritumoral tissue and in RWPE-1 cells, respectively. The results showed that cir-ITCH overexpression significantly inhibits the proliferation, migration, and invasion of human PCa cells and that reciprocal inhibition of expression occurred between cir-ITCH and miR-17. Proteins in the Wnt/ β -catenin and PI3K/AKT/mTOR pathways were downregulated by overexpression of cir-ITCH both in androgen receptor-positive LNCaP cells and androgen receptor-negative PC-3 cells. Taken together, these data demonstrated that cir-ITCH plays a tumor-suppressive role in human PCa cells, partly through the Wnt/ β -catenin and PI3K/AKT/mTOR pathways. Thus, cir-ITCH may serve as a novel therapeutic target for the treatment of PCa, especially castration-resistant prostate cancer.